2020
DOI: 10.1038/s41598-020-69691-8
|View full text |Cite
|
Sign up to set email alerts
|

Survival differences and associated molecular signatures of DNMT3A-mutant acute myeloid leukemia patients

Abstract: Acute myeloid leukemia (AML) is a very heterogeneous and highly malignant blood cancer. Mutations of the DNA methyltransferase DNMT3A are among the most frequent recurrent genetic lesions in AML. The majority of DNMT3A-mutant AML patients shows fast relapse and poor survival, but also patients with long survival or long-term remission have been reported. Underlying molecular signatures and mechanisms that contribute to these survival differences are only poorly understood and have not been studied in detail so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 87 publications
2
13
0
Order By: Relevance
“…Lauber et al believed that the expression of miR-6718 in patients with acute myeloid leukemia was significantly different from that of normal individuals, so the prognosis of patients with acute myeloid leukemia could be determined by the difference in miR-6718 expression. 17 However, no relevant studies on miR-6718 and patients with AMI have been conducted thus far. In this study, it was found that the expression of miR-6718 in patients with AMI was significantly lower than that in normal individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Lauber et al believed that the expression of miR-6718 in patients with acute myeloid leukemia was significantly different from that of normal individuals, so the prognosis of patients with acute myeloid leukemia could be determined by the difference in miR-6718 expression. 17 However, no relevant studies on miR-6718 and patients with AMI have been conducted thus far. In this study, it was found that the expression of miR-6718 in patients with AMI was significantly lower than that in normal individuals.…”
Section: Discussionmentioning
confidence: 99%
“…More details to the underlying concept are provided in [ 24 , 68 ]. Following [ 71 ], this network inference was repeated 100 times based on randomly created training sets that comprised 75% of all 87 CML gene expression samples (i.e., 65 randomly selected CML samples). The other 25% of samples (i.e., the remaining 22 CML samples), which were not in the corresponding specific training set, were considered as independent network-specific test set.…”
Section: Methodsmentioning
confidence: 99%
“…Chromatin regulators have been identified as drivers of transformation in various blood malignancies. Chromosomal rearrangements (e.g., MLL rearrangements ( MLL -r) in acute myelogenous leukemia (AML) or BCR–ABL1 in chronic myelogenous leukemia (CML)) and mutations (point mutations in EZH2 in acute lymphocytic leukemia (ALL)) can affect chromatin state [ 19 , 20 , 21 , 22 , 23 ] and/or activity of the enzymes involved in methylation/demethylation or acetylation/deacetylation of chromatin. These modifications are important for the activation or suppression of transcription ( Table 1 ).…”
Section: Epigenetics: General Considerationsmentioning
confidence: 99%